Vocab heroes website : Digital transformation in the new way of teaching vocabulary / Savina A. Saiman ... [et al.] - A.Saiman, Savina; Mat Johari, Muhammad Naim; Mohd Shuib, Siti Aishah; Shamsuddin, Nur Asharina Balqis (2023)
The 'Vocab Heroes Website' is not only to save time but also to inspire language teachers and learners. It has been observed that many students are not able to use low-frequency words, especially at B2, C1 and C2 levels, in their texts, which can put them in a high level for MUET. Designed to help students write confidently and correctly and produce exceptional essays in English, the Vocab Heroes website is one of the technologies used for teaching in both virtual and physical classrooms. In addition, the website is a modern teaching tool that provides tips and explanations to help students use low-frequency words appropriately by including elements such as cartoon voices, colourful graphics, interactive videos, lists of B2-C2 words according to the topics and quizzes. It encourages and promotes critical thinking, collaborative problem solving and social and technical progress through trial and error. We believe that education should be available to everyone, even those without internet access, so that we can achieve our goal and mission of immersing our students in the diversity of English words. This is our original website with manual interactive games. This new way of teaching will not only engage students in learning the language but it will indirectly help the teachers who can also use it as their new method in teaching.